ETNOMATEMÁTICA E DOCÊNCIA: POSSIBILIDADES DE ATUAÇÃO NUMA ESCOLA EM UMA COMUNIDADE REMANESCENTE QUILOMBOLA - ODÉCIO JUNIOR BATISTA MARTINS (2024)
In this research, our main objective is to analyze the possibilities for Mathematics teachers to work in a quilombola school and the possible ways of relating the subject to the sociocultural context of their students. The work was carried out with three teachers from the Zumbi dos Palmares State School, located in the rural area of ​​Jaraguari, in a remaining quilombola community in Mato Grosso do Sul, but which does not offer Quilombola School Education. As a theoretical framework, we propose Ethnomathematics, which has in its essence the study of the cultural manifestations of individuals and groups, knowing and echoing their knowledge - among them the ways of mathematizing - and also investigating how they construct their knowledge. This was a qualitative research approach, the data was produced through semi-structured interviews with Mathematics teachers who work/worked at the school. Braun and Clarke's Thematic Analysis (2006) was used to analyze the data. The themes are selected based on reading the data produced and evaluating the potential that each of them has to produce an understanding of the research object. Through the analysis carried out, we were able to discuss topics that interfere in the actions of teachers who work in a quilombola school, such as initial and continuing training, teaching material, the inclusion of students' culture in Mathematics classes and the differences between a school quilombola and other schools. Keywords: Mathematics Education, Ethnomathematics, Rural Education, Quilombola School, Teaching.